NURSING TELECONSULTATION IN WOMEN'S HEALTH: SITUATIONAL DIAGNOSIS OF PRIMARY CARE IN THE CITY OF BEZERROS-PE (Interdisciplinary Studies Journal, 2025)
This study aimed to execute a situational diagnosis of Primary Care services for the implementation of nursing teleconsultation in women's health, in the city of Bezerros-PE. This is a quantitative study of an exploratory nature, in order to identify problems, needs and determining factors in the area of ​​women's health. The study sites were the Núcleo de Telessaúde do Centro Universitário Integrado Amaury de Medeiros (NUTES-CISAM) of the University of Pernambuco (UPE) and the basic health units of the city of Bezerros, with the study population being nurses from the units. The sample was of the intentional non-probabilistic type. It resulted in the participation of 18 nurses, observing a favorable scenario for the integration of teleconsulting, where, despite limitations, it raised all interests in the strategy. It is concluded that teleconsulting can be beneficial to increase the resolution of UBS, as there is interest and demand from professionals to adhere to it.
Keywords: Telemedicine; Digital Technology; eHealth Strategies; Public Health Nursing; Maternal and Child Nursing